Robust sulfur and oxygen isotope evidence for a highly anoxic paleoenvironment in Late Devonian seawater: Insights from marine anhydrites in the Zaige Formation, South China - Shu, Xiaochao; Meng, Fanwei; Liang, Kun (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
A global-scale mass extinction event occurred in the Late Devonian, and its triggering mechanisms have remained a subject of controversy. The key to resolving this controversy lies in elucidating paleoenvironmental characteristics and their coupling relationship with the mass extinction. Marine evaporites serve as sensitive indicators that can be used for reconstructing the geochemical history of ancient oceans. In this study, we present a dual sulfur and oxygen isotopic dataset of marine anhydrites in the Lunatian gypsum deposit (Yunnan, China), and investigate its paleoenvironmental significance within the framework of the Late Devonian mass extinction. These anhydrites originate in arid and hot continental margin seas near convergent plate boundaries, forming as a result of the dehydration of marine gypsums during burial processes. Anhydrites exhibit a conspicuous positive anomaly in δ34S values (23.6–25.1‰, averaging 24.3‰), primarily attributed to bacteria-mediated sulfate reduction. The δ18O values of the Lunatian anhydrites (12.2–15.2‰, averaging 14.0‰) indicate a slightly higher oxygen isotope composition for Late Devonian seawater (8.7–11.7‰, averaging 10.5‰) compared to those of contemporary seawater (9.5–10.1‰). Such an oxygen isotopic characteristic for the Lunatian anhydrites is intricately associated with the chemical processes that occur during the diffusion of sulfides into the upper seawater. The anhydrite-forming evaporating system has a noticeable brine layering where the surface seawater is less dense than the deeper brine, and bacterial processes gradually increase δ34S in the deep brine. When the deep brine and surface seawater rapidly mix, it leads to a significant positive shift in the sulfur isotope composition of the resulting evaporites. Our sulfur and oxygen isotope data from Lunatian anhydrites validate the existence of an exceedingly anoxic marine environment during the Late Devonian, potentially serving as a pivotal factor in the mass extinction event. Schematic diagrams showing (a) the sedimentary environment and diagenetic processes of the Lunatian anhydrites, (b) three strong positive anomaly events of sulfur isotopes of global seawater since the Phanerozoic, and (c) plots of the measured δ34S vs. δ18O data for the Lunatian anhydrites. [Display omitted] •Late Devonian seawater shows a significant positive anomaly of sulfur isotope.•Bacterial reduction activity led to the elevated sulfur isotope levels of seawater.•Anoxia in paleoenvironment is a key driver of the Late Devonian mass extinction.•Sulfur isotope analysis of evaporites can swiftly identify Late Devonian strata.